Just a sound: A non-pharmacological treatment approach in epilepsy - Igor Timofeev (Elsevier, 2021)
Benign epilepsy with centro-temporal spikes is typically not treated by antiepileptic drugs, but it leads to cognitive disfunctions. In this issue, Klinzing et al.1 demonstrate that closed-loop auditory stimulation delivered after paroxysmal spikes reduces the total number of paroxysmal spikes.